Decreasing brain activity caused by acute administration of ketamine and alcohol – A randomized, controlled, observer-blinded experimental study - Ferreira, Luan Oliveira; Padilha da Silveira, Esther; Paz, Clarissa A.; Otake Hamoy, Maria K.; Barbosa, Gabriela B.; Santos, Murilo F.; Conceição, Raína M.; Amaral, Anthony Lucas G.; Resende, Karina Dias; Favacho Lopes, Dielly Catrina; Hamoy, Moisés (Frontiers in Pharmacology, 2024)
Introduction Substance abuse is a major public health problem. In recent years, ketamine, which is a parenteral anesthetic, has been consumed increasingly as an illicit drug together with alcohol, although little is known of how this association alters brain activity. The present study investigated the influence of progressive doses of ketamine, associated with alcohol, on electrophysiological activity. Methods For this, 72 late-adolescent (8–10-week-old) male Wistar rats received either ketamine only, at low (10 mg/kg), intermediate (20 mg/kg) or high (30 mg/kg) doses via intraperitoneal injection, or alcohol (2 mL/100 g) via oral gavage followed by ketamine (at low, intermediate, and high doses). Electroencephalograms (EEG) and electromyographic recordings were obtained 5 min after the final application of the drug. Results When administered alone, ketamine resulted in an increase in delta, theta, beta, and gamma brainwaves, with a more pronounced effect being detected at the highest dose (30 mg/kg) in the case of the delta, beta, and gamma waves. The amplitude of the alpha brainwaves was reduced at all doses of ketamine, but less intensively at the highest dose. When administered alone, alcohol reduced all the brainwaves, with the reduction in the alpha waves being exacerbated by ketamine at all doses, and that of the theta and beta waves being boosted at the lowest dose. The intermediate dose of ketamine (20 mg/kg) reverted the alcohol-induced reduction in the theta and gamma waves, whereas the high dose increased delta, theta, beta, and gamma bandpower. Discussion Overall, then, while ketamine enhances the depressant effects of alcohol on the alpha brainwave at all doses, a low dose intensified this effect on the theta and beta 175 waves, whereas a high dose produces neuronal hyperexcitability in the theta and 176 gamma bandpower.